Reincarnating the Identity Theory - Myin, Erik; Zahnoun, Farid (Frontiers in Psychology, 2018)
The mind/brain identity theory is often thought to be of historical interest only, as it has allegedly been swept away by functionalism. After clarifying why and how the notion of identity implies that there is no genuine problem of explaining how the mental derives from something else, we point out that the identity theory is not necessarily a mind/brain identity theory. In fact, we propose an updated form of identity theory, or embodied identity theory, in which the identities concern not experiences and brain phenomena, but experiences and organism-environment interactions. Such an embodied identity theory retains the main ontological insight of its parent theory, and by invoking organism-environment interactions, it has powerful resources to motivate why the relevant identities hold, without posing further unsolvable problems. We argue that the classical multiple realization argument against identity theory is built on not recognizing that the main claim of the identity theory concerns the relation between experience and descriptions of experience, instead of being about relations between different descriptions of experience and we show how an embodied identity theory provides an appropriate platform for making this argument. We emphasize that the embodied identity theory we propose is not ontologically reductive, and does not disregard experience.